Techno-economic analysis of hydrothermal carbonization of sewage sludge for phosphorus retention and carbon sequestration - Osama Khoury; Sabrina Spatari; Roy Posmanik (Waste Management, 2026)

Sustainable pharmaceutical manufacturing based on mechanochemistry: A life cycle assessment of rac-Ibuprofen-Nicotinamide cocrystallization routes - Michael Patrascu; Damiana Meuti; Or Galant; Sally Nijem; Charles E. Diesendruck; Andrea Casagrande; Evelina Colacino; Michael Felderhoff; Sabrina Spatari (Sustainable Chemistry and Pharmacy, 2026)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Assessing the Potential of Biodegradable Plastics in a Circular Economy: A Methodological Outlook - Quinten Scheers; Philippe Nimmegeers; Or Galant; Sabrina Spatari; Niko Van den Brande; Joost Brancart; Pieter Billen (Circular Economy and Sustainability, 2025)

When floodplain restoration meets socio‐ecological goals for rural stormwater management - Lisa A. Peterson; Patricia M. Awerbuch; Sabrina Spatari (Journal of Industrial Ecology, 2025)
Floodplain restoration is an approved stormwater management method, but rarely chosen by developers due to the perceived high cost and lengthy approvals required from regulatory agencies. Yet, when chosen, restoring a floodplain yields significant environmental benefits for the community due to improved flood resiliency and wetland habitat and superior reduction of negative externalities. In 2012, a corporation in Lancaster County, Pennsylvania, explored the option to restore a historic floodplain on its 40‐hectare property to fulfill the stormwater management requirements for a planned development project. There was a social dynamic at play in this instance that allowed the developer, municipality, and citizens to achieve a win across three dimensions often in conflict: maximizing private economic returns, achieving environmental compliance, and benefiting the community ecologically. Using a social–ecological system (SES) framework, this paper analyzes the course of the development project through the government approvals process and the actual restoration of the floodplain. Two influential actors are identified who do not often appear in the literature on SESs: sports advocacy groups and religious groups. We posit that the developer's industry was uniquely receptive to conservation appeals and that the proximity of an urban metropolis made collective action a relevant strategy for the region. Critical factors in the decision process were the cost–benefit analysis contracted by the developer, local (county) government leadership, and a history of local citizen activism. We conclude that a misalignment of anthropogenic and ecological boundaries can prevent such positive outcomes and that collective action is a viable strategy to overcome that challenge.

Meeting sustainable aviation fuel policy targets through first generation corn biorefineries - Rahamim Batten; Or Galant; Mukund Karanjikar; Sabrina Spatari (Fuel, 2023)

Life cycle assessment and techno-economic analysis of nitrogen recovery by ammonia air-stripping from wastewater treatment - Saurajyoti Kar; Rajveer Singh; Patrick L. Gurian; Adam Hendricks; Paul Kohl; Sean McKelvey; Sabrina Spatari (Science of The Total Environment, 2023)

Evaluating life cycle environmental impacts of coal fly ash utilization in embankment versus sand and landfilling - Sarah Curpen; Nadya Teutsch; Konstantin Kovler; Sabrina Spatari (Journal of Cleaner Production, 2023)

Is aquaponics good for the environment?—evaluation of environmental impact through life cycle assessment studies on aquaponics systems - Asael Greenfeld; Nir Becker; Janet F. Bornman; Sabrina Spatari; Dror L. Angel (Aquaculture International, 2022)

Environmental and economic implications of stormwater management alternatives in rural development - Lisa A. Peterson; Patricia M. Awerbuch; Sabrina Spatari (Journal of Industrial Ecology, 2021)
Floodplain restoration as a means of stormwater management (SWM) can benefit communities and the environment but is uncommonly chosen due to limited familiarity in rural and urban planning. This study uses life cycle assessment and life cycle costing (LCC) to compare four SWM alternatives for a typical rural setting undergoing development. We evaluate a case study in Lancaster County, PA in the Chesapeake Bay Watershed which, through community stakeholder planning, undertook a novel SWM plan by restoring its historic floodplain. We evaluate the life cycle impact assessment (LCIA) metrics, global warming (GW), eutrophication and acidification and cost for each alternative over a 100‐year period of analysis including construction, maintenance, and end‐of‐life decommissioning. Assuming a 5% discount rate, and that soils do not require off‐site hauling due to contamination, the cost and LCIA metrics for floodplain restoration are not significantly higher than the more conventional surface basin alternative. Although LCC is highly sensitive to the transport of soil off‐site, more than doubling the costs for the underground stormwater infiltration basin (USIB) and increasing eightfold the cost for the floodplain restoration, contaminated soil removal is rarely needed on rural land. For USIB, LCIA metrics are sensitive to the choice of recycling versus incinerating plastic components, with recycling resulting in lower GW; and for the permeable pavement alternative, additional maintenance to extend its lifetime shows favorable cost and reduced GW. We conclude that in rural settings where soil is not contaminated, floodplain restoration offers environmental and social benefits for SWM that outweigh its costs.

Framework for improved confidence in modeled nitrous oxide estimates for biofuel regulatory standards - Shuang Gao; Patrick L. Gurian; Paul R. Adler; Sabrina Spatari; Ram Gurung; Saurajyoti Kar; Stephen M. Ogle; William J. Parton; Stephen J. Del Grosso (Mitigation and Adaptation Strategies for Global Change, 2018)

Estimating Materials Stocked by Land‐Use Type in Historic Urban Buildings Using Spatio‐Temporal Analytical Tools - Kimberlee A. Marcellus‐Zamora; Patricia M. Gallagher; Sabrina Spatari; Hiroki Tanikawa (Journal of Industrial Ecology, 2016)
Summary The construction industry is an important contributor to urban economic development and consumes large volumes of building material that are stocked in cities over long periods. Those stocked spaces store valuable materials that may be available for recovery in the future. Thus quantifying the urban building stock is important for managing construction materials across the building life cycle. This article develops a new approach to urban building material stock analysis (MSA) using land‐use heuristics. Our objective is to characterize buildings to understand materials stocked in place by: (1) developing, validating, and testing a new method for characterizing building stock by land‐use type and (2) quantifying building stock and determining material fractions. We conduct a spatial MSA to quantify materials within a 2.6‐square‐kilometer section of Philadelphia from 2004 to 2012. Data were collected for buildings classified by land‐use type from many sources to create maps of material stock and spatial material intensity. In the spatial MSA, the land‐use type that returned the largest footprint (by percentage) and greatest (number) of buildings were civic/institutional (42%; 147) and residential (23%; 275), respectively. The model was validated for total floor space and the absolute overall error (n = 46; 20%) in 2004 and (n = 47; 24%) in 2012. Typically, commercial and residential land‐use types returned the lowest overall error and weighted error. We present a promising alternative method for characterizing buildings in urban MSA that leverages multiple tools (geographical information systems [GIS], design codes, and building models) and test the method in historic Philadelphia.

Using Life Cycle Assessment to Evaluate Green and Grey Combined Sewer Overflow Control Strategies - Maria R. C. De Sousa; Franco A. Montalto; Sabrina Spatari (Journal of Industrial Ecology, 2012)
Summary Decentralized approaches to managing urban stormwater are gaining increased attention within the contexts of urban sustainability, climate change adaptation, and as a means of reducing combined sewer overflows (CSOs). This study applied a life cycle assessment (LCA) to comparing the environmental efficiency of three means of equivalently reducing CSOs to the Bronx River (Bronx, NY, USA). Strategy 1 featured decentralized green infrastructure technologies, while “grey” strategies 2 and 3 detained, and detained and treated, respectively, excess flows at the end of pipe. We estimated greenhouse gas emissions (in metric tons of carbon dioxide equivalents [t CO 2 ‐eq]) over the construction, operation, and maintenance phases, including energy consumed at the wastewater treatment plant (WWTP), carbon sequestered, and shading provided by vegetation (in the case of the green approach) over a 50‐year analysis period. The study area comprised the entire drainage area contributing to New York State permitted CSO discharge points associated with the Hunts Point WWTP. The analysis was performed using a hybrid of process and economic input‐output (EIO) LCA methods. The decentralized green strategy outperformed the two grey strategies in terms of this set of environmental metrics. The net emissions of the green strategy over 50 years was 19,000 t CO 2 ‐eq, whereas the grey strategies emitted 85,000 t CO 2 ‐eq (detention) and 400,000 t CO 2 ‐eq (detention and treatment). These results were significantly influenced by the emissions associated with the operation and maintenance activities required for strategies 2 and 3, and the carbon sequestered and shading provided by the vegetation in strategy 1, and suggest that watershed managers who seek to reduce CSOs and reduce carbon footprints would opt for the green approach.

The Multilevel Cycle of Anthropogenic Zinc - T. E. Graedel; Dick van Beers; Marlen Bertram; Kensuke Fuse; Robert B. Gordon; Alexander Gritsinin; Ermelinda M. Harper; Amit Kapur; Robert J. Klee; Reid Lifset; Laiq Memon; Sabrina Spatari (Journal of Industrial Ecology, 2005)
Summary A comprehensive annual cycle for stocks and flows of zinc, based on data from circa 1994 and incorporating information on extraction, processing, fabrication, use, discard, recycling, and landfilling, was carried out at three discrete governmental unit levels—54 countries and 1 country group (which together comprise essentially all global anthropogenic zinc stocks and flows), nine world regions, and the planet as a whole. All of these cycles are available in an electronic supplement to this article, which thus provides a metadata set on zinc flows for the use of industrial ecology researchers. A “best estimate” global zinc cycle was constructed to resolve aggregation discrepancies. Among the most interesting results are the following: (1) The accumulation ratio, that is, addition to in‐use stock as a function of zinc entering use, is positive and large (2/3 of zinc entering use is added to stock) (country, regional, and global levels); (2) secondary input ratios (fractions of input to fabrication that are from recycled zinc) and domestic recycling percentages (fractions of discarded zinc that are recycled) differ among regions by as much as a factor of six (regional level); (3) worldwide, about 40% of the zinc that was discarded in various forms was recovered and reused or recycled (global level); (4) zinc cycles can usefully be characterized by a set of ratios, including, notably, the utilization efficiency (the ratio of manufacturing waste to manufacturing output: 0.090) and the prompt scrap ratio (new scrap as a fraction of manufacturing input: 0.070) (global level). Because capturable discards are a significant fraction of primary zinc inputs, if a larger proportion of discards were recaptured, extraction requirements would decrease significantly (global level). The results provide a framework for complementary studies in resource stocks, industrial resource utilization, energy consumption, waste management, industrial economics, and environmental impacts.

Using GaBi 3 to perform life cycle assessment and life cycle engineering - Sabrina Spatari; Michael Betz; Harald Florin; Martin Baitz; Michael Faltenbacher (The International Journal of Life Cycle Assessment, 2001)

Application of life cycle inventory analysis to fuel tank system design - Gregory A. Keoleian; Sabrina Spatari; Robb T. Beal; Robert D. Stephens; Ronald L. Williams (The International Journal of Life Cycle Assessment, 1998)